2016
DOI: 10.1111/micc.12256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1α‐Calcidol (Alfacalcidol) on Microvascular Endothelial Function, Arterial Stiffness, and Blood Pressure in Type II Diabetic Nephropathy Patients

Abstract: Alfacalcidol did not have an effect on microvascular endothelial function in DN patients. Alfacalcidol significantly improved CSBP with trends of improvement in arterial stiffness and peripheral BP. Alfacalcidol appears to be more beneficial in vitamin D-deficient patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Thus, evidences on the ability of antioxidants to regulate oxidative stress in diabetes are compelling and suggests potential additional treatment strategy to reduce cardiovascular risk and complications in diabetes. In view that vitamin D supplementation is able to improve many cardiovascular biomarkers in both diabetic (78,110) and non-diabetic (111) population with vitamin D deficiency, it may be a potential measure in regulating oxidative stress underlying diabetic complications. By correcting the vitamin D levels as shown by accumulating evidences in epidemiology studies, enhanced oxidative damage and reduced antioxidant activities might be reversed or at least improved in diabetic population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, evidences on the ability of antioxidants to regulate oxidative stress in diabetes are compelling and suggests potential additional treatment strategy to reduce cardiovascular risk and complications in diabetes. In view that vitamin D supplementation is able to improve many cardiovascular biomarkers in both diabetic (78,110) and non-diabetic (111) population with vitamin D deficiency, it may be a potential measure in regulating oxidative stress underlying diabetic complications. By correcting the vitamin D levels as shown by accumulating evidences in epidemiology studies, enhanced oxidative damage and reduced antioxidant activities might be reversed or at least improved in diabetic population.…”
Section: Discussionmentioning
confidence: 99%
“…In the development of adverse cardiovascular events, especially in DM, low vitamin D level is suggested as one of the risk factors (59). This is supported by statistics showing high prevalence of vitamin D insufficiency and deficiency occurring in the diabetic population; 91.1% in India (76), 73.6% in Saudi Arabia (77) and 43% in Malaysia (78).Studies have shown that higher vitamin D levels were associated with 40% lower risk of T2DM in women while subjects that developed diabetes had lower vitamin D levels (serum 25(OH)D < 50 nmol/L) compared to non-diabetics (79). This suggested that low circulating vitamin D concentrations played a significant role in the pathogenesis of DM.…”
Section: Vitamin D Status and Diabetes Mellitusmentioning
confidence: 94%
“…In contrast to this finding, no significant correlation between vitamin D levels and UACR has been reported by other research groups, which might be explained by the small number of study patients in these trials [ 53 , 56 ]. Several well-designed observational and interventional studies have shown a recovery of renal function after vitamin D therapy [ 27 , 56 , 62 , 63 , 64 , 65 ], which was not confirmed by others [ 25 , 53 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 87%
“…In addition to the higher risk of DN in patients with vitamin D deficiency, multiple interventional studies have shown a recovery of renal function after vitamin D therapy [ 27 , 56 , 62 , 63 , 64 , 65 ]. An RCT was performed in 48 T1DN patients to examine the effects of a 12-week paricalcitol treatment (starting dose was 1 µg daily if plasma parathyroid hormone levels were <53 pmol/L (<500 pg/mL), or, if higher, the starting dose was 2 µg paricalcitol daily) on renal function [ 62 ].…”
Section: Human Studiesmentioning
confidence: 99%
“…After intervention, SBP and DBP in vitamin D group (n=30, BP from 121/80.5 to 110/76.3 mm Hg) was significantly decreased compared with those in placebo group (n=30). Munisamy et al [86] randomly assigned 70 normotensive type 2 diabetes patients receiving either 0.25 μg α-calcidol daily (n=34) or placebo (n=36) for 6 months. In the end of the study, α-calcidol (n=28) significantly reduced central SBP.…”
Section: Effect Of Vitamin D Administration On Bp In Vitamin D-deficimentioning
confidence: 99%